1999
DOI: 10.1128/jcm.37.6.1752-1757.1999
|View full text |Cite
|
Sign up to set email alerts
|

Density and Molecular Epidemiology of Aspergillus in Air and Relationship to Outbreaks of Aspergillus Infection

Abstract: After five patients were diagnosed with nosocomial invasive aspergillosis caused by Aspergillus fumigatus andA. flavus, a 14-month surveillance program for pathogenic and nonpathogenic fungal conidia in the air within and outside the University Hospital in Rotterdam (The Netherlands) was begun. A. fumigatus isolates obtained from the Department of Hematology were studied for genetic relatedness by randomly amplified polymorphic DNA (RAPD) analysis. This was repeated with A. fumigatus isolates contaminating cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(33 citation statements)
references
References 25 publications
6
25
0
2
Order By: Relevance
“…The CFU was increased in summer as reported by other studies. 18,19 In contrast, Goodley et al [20] did not report seasonal variations.…”
Section: Discussionmentioning
confidence: 96%
“…The CFU was increased in summer as reported by other studies. 18,19 In contrast, Goodley et al [20] did not report seasonal variations.…”
Section: Discussionmentioning
confidence: 96%
“…Other studies encountered Aspergillus spp. as the most frequent genus (Leenders et al 1999;Augustowska and Dutkiewicz 2006). Differences among the published data may be expected because of differences in geographical location, climate characteristics, season of the year, presence of accumulated dust, carbon dioxide concentration, presence of air conditioning system and other conditions.…”
Section: Institution Speciesmentioning
confidence: 99%
“…In contrast, Pandita et al 13 observed only 25% mortality in quail chickens challenged intratracheally by conidia of A. flavus. These conflicting results, and the dearth of experimental studies on disseminated aspergillosis caused by A. flavus, although this species is frequently implicated in this condition 1,28,29 , prompted our attempt to develop and to characterize an experimental model of disseminated aspergillosis caused by A. flavus.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi of the genus Aspergillus are ubiquitous, and their conidia abound in relatively uniform numbers in the outside air throughout the year. 1 Inhalation of these airborne conidia by immunocompromised patients, such as those with haematological malignancies or those undergoing liver transplantation, may result in severe disseminated disease. 2,3 In fact, the predominant cause of visceral mycoses in Japan in the period 1991-94 was found to be Aspergillus spp.…”
Section: Introductionmentioning
confidence: 99%